Experimental and numerical investigation of additively manufactured novel compact plate-fin heat exchanger. (July 2022) - Ning, Jiuxin; Wang, Xiaodong; Sun, Yajing; Zheng, Chenggang; Zhang, Shengwu; Zhao, Xi; Liu, Changyong; Yan, Wentao
Highlights: Novel compact plate-fin heat exchangers fabricated by laser powder bed fusion (LPBF) Experimental and numerical investigation of different plate-fin heat exchangers Plate-fin heat exchanger with twisted fins exhibits superior thermal performance Improved rectangular fins improve coefficient of performance and overall performance Abstract: Plate-fin heat exchanger (PFHX) is one of the vital compact heat exchangers due to its high heat transfer area per unit volume and promising potentials in industrial applications where dimensions and weight are limited. Additive manufacturing presents great potentials for fabricating novel compact heat exchangers. In this work, three types of compact heat exchangers including a PFHX with twisted fins, a PFHX with improved rectangular fins and a PFHX with conventional rectangular fins are manufactured using the laser powder bed fusion (LPBF) technology. The experimental tests together with numerical simulations are conducted to evaluate the thermal performance and pressure drop of the heat exchangers. The results show that PFHX with twisted fins exhibits superior thermal performance among the three heat exchangers, and the PFHX with improved rectangular fins has the highest experimental coefficient of performance (COP) and provides outstanding overall performance. Furthermore, the impact of LPBF accuracy on the performance of heat exchanger are discussed to provide guidance for future designs.